2017
DOI: 10.1016/j.fsi.2017.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny and modulation after PAMPs stimulation of β-defensin, hepcidin, and piscidin antimicrobial peptides in meagre ( Argyrosomus regius )

Abstract: Antimicrobial peptides (AMPs), components of innate immunity, play an important role in protecting fish. In this study we report the molecular cloning of full open reading frames and characterization of expression of three AMP genes (β-defensin (defb), hepcidin (hep2), piscidin (pisc) in meagre (Argyrosomus regius). A phylogenetic analysis of the expressed sequences obtained shows the defensin isoform forms a clade with the other members of the beta class of this family, hepcidin corresponds to hepcidin 2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…AMPS can be majorly divided into different families which include defensin, parasin, cathelicidin and hepcidin, and piscidin. These AMP families are species-specific, with piscidin being unique to teleost fish (Campoverde et al 2017). Table 3 outlines the specific MEC and MIC values for fish skin peptides with antimicrobial activity along with their sequences.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…AMPS can be majorly divided into different families which include defensin, parasin, cathelicidin and hepcidin, and piscidin. These AMP families are species-specific, with piscidin being unique to teleost fish (Campoverde et al 2017). Table 3 outlines the specific MEC and MIC values for fish skin peptides with antimicrobial activity along with their sequences.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…It has been found that the two hepcidin peptides identified in teleost fish show a degree of sub functionalization of its functions, where hepcidin 1 (HAMP1) more implicated in iron metabolism regulation and hepcidin 2 (HAMP2) mainly performing an antimicrobial role (Neves et al 2015). The AMP production go through a main pathway by the recognition of pathogen-associated molecular patterns (PAMPs) through receptors (PRRs), such as Toll-like receptors (TLRs), exciting a cascade of intracellular signaling involving MyD88, TRAF6, IRAK1, and IKK that promotes the activation and translocation of NF-kB to the nucleus where it transcriptionally stimulates AMPs and other effector molecules (Campoverdea et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial peptides (AMPs) are small size molecules (less than 100 aa) with antimicrobial activity, belonging to the innate immune system in teleosts (Campoverde et al, ; Casadei et al, ; Secombes & Wang, ; Zou, Mercier, Koussounadis, & Secombes, ). Many cells in the lining epithelial surface, such as in gill, skin, and gut, secrete AMPs (Campoverde et al, ; Secombes & Wang, ; Zou et al, ). After being challenged with the Gram negative Yersinia ruckeri , the expression of the AMP ß‐defensins (BD‐3 and BD‐4) showed a significant increase in the blood of rainbow trout (Monte, Urquhart, Secombes, & Collet, ).…”
Section: Introductionmentioning
confidence: 99%
“…After being challenged with the Gram negative Yersinia ruckeri , the expression of the AMP ß‐defensins (BD‐3 and BD‐4) showed a significant increase in the blood of rainbow trout (Monte, Urquhart, Secombes, & Collet, ). Recently, several novel teleost ß‐defensin s were identified and detected by RT‐PCR from rainbow trout (Casadei et al, ), zebrafish (Zou et al, ), and meagre (Campoverde et al, ). Defensins are important peptides with immunomodulatory function and represent an important linking factor between innate and adaptive immunity (Campoverde et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation